The Very Hungry Caterpillar - Koch, Priyanka; Sharma, Hitesh (Voices of Teachers and Teacher Educators, 2023)
Illustrations are beautiful because they open a whole new world to the little children where every creativity finds expressions. It is like that by giving them books we are providing them a space for the open expressions of their thoughts. Use of illustrations in the early years is crucial. The scribble marks of children are never to be ignored. The books provided to children in the Foundational years need to be simple and should have the ability to illuminate young minds. Everything that the child sees in his immediate environment attracts his/her attention. They imitate a cartoon character in the T.V and also starts humming to the sounds that they hear around. This happens in the foundational years because children are involved in the process of observation. The contextualisation is also very much relevant when it comes to using the books in the foundational years. It is also one of the best ways through which children can be connected to nature and also for making them effective communicators.